Lockup: a credible IPO signal? - Lim, Francine Siew Koon (2008)
This paper examines whether lock-up is a signaling mechanism used by insiders of IPO firms in order to convey the quality of the firm, using a sample of 315 IPOs in Singapore, which occurred between 1990 and 2000.